Indonesia INTRERAKSI OBAT PADA PASIEN DIABETES MELITUS:TINJAUAN SISTEMATIS STUDI DI INDONESIA(2020-2025) - Trirahmi Hardiyanti; Rahma Dita; Annisa Syahrani; Nasyiah Tri Naurah; Evi Susanti (Sekolah Tinggi Ilmu Kesehatan Madani Yogyakarta, 2025)
Drug interactions are a major challenge in managing therapy for diabetes mellitus patients who often experience polypharmacy. This study aims to evaluate the prevalence, types, and clinical impacts of drug interactions reported in various studies in Indonesia over the past five years. A systematic method was conducted by searching articles from Google Scholar databases published between 2020 and 2025. Inclusion criteria included observational and experimental studies on pharmacotherapeutic interactions in patients diagnosed with diabetes mellitus in Indonesia. Of the 582 articles identified, 10 studies met the inclusion criteria. Results showed that interactions between metformin and antihypertensive drugs were the most commonly reported. The clinical impacts found included an increased risk of hypoglycemia and impaired kidney function. These findings highlight the importance of therapeutic monitoring and collaboration between pharmacists and healthcare professionals to reduce the risk of drug interactions. Keywords: Diabetes Mellitus, Drug Interactions, Polypharmacy